Faktor Penentu yang Mempengaruhi Profitabilitas Perusahaan Asuransi yang Terdaftar di Indonesia pada Tahun 2017-2022 - Aristianti, Aldelia Putri; Rahayu, Ismi Kurnia Ningsih; Alfarizki, Alfad; Leon, Farah Margaretha (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This study aims to identify variables that affect profitability in insurance companies listed in Indonesia. The addition of reinsurance variable as an independent variable is the novelty part of this research. The research method involves collecting data from 20 insurance companies over a 6-year period (2017-2022) and applying data processing analysis using panel data regression analysis techniques. The results found that loss ratio has a positive impact on ROA, while tangibility and managerial efficiency have a negative impact on ROA. In addition, age, leverage, liquidity, size, GDP growth, inflation, premium growth and reinsurance have no significant effect on ROA. The implication for financial managers is to choose the best way to utilize assets in order to achieve business goals. This research emphasizes the importance of loss ratio, managerial efficiency, & asset tangibility for investors when choosing investment opportunities in insurance companies.